Comorbidades de transtornos mentais e comportamentais entre pacientes com dependência química em diferentes períodos de abstinência - Costa, Maria de Lourdes Pereira (2011)
Introduction: Patients with psychoactive substance (PAS) dependence may co-present other mental and behavioral disorders (MBD), and such comorbidities may alter the symptoms and interfere with proper diagnosis, treatment and prognosis of each disease. Objectives: We aimed to assess the frequency of MBD comorbidities in patients dependent on PAS attending Centers for Psychosocial Care alcohol and other drugs (CAPS-ad), and their feelings about their own use of these substances. Furthermore, we aimed to compare socio-demographic data, conditions related to childhood and clinical features between those patients with and without comorbidities. Method: We consecutively analyzed adult patients from April to September, 2010, in two CAPS-ad in Uberlândia MG, excluding those who were under the influence of PAS, with withdrawal symptoms or with dementia. Patients were divided according to the abstinence length: < 1 week (Group 1), 1 to 4 weeks (Group 2) and > 4 weeks (Group 3). For diagnosing comorbidities we used the symptoms checklist of ICD-10 and collected information from medical records. We used a structured questionnaire to collect the analyzed data. Results: Among the 188 evaluated patients, 62.8% were diagnosed with a MBD comorbidity, which were more frequent (p < 0.05) in Group 1 (72%) than in Group 3 (54.2%), and what differed them was the greater frequency of depressive disorders and other anxiety disorders in the first (61.3% and 34.6% respectively); both groups were similar to Group 2 (61.0%). Patients with comorbidities, more often than those without them, respectively, suffered abuse in childhood (67.8% and 42.8%), had perceived that presented another MBD (84.7% and 37.1%) and psychological disorders (79.7% and 44.3%) in addition to CD, made use of psychotropic medications (81.4% and 37.1%) and previous treatments for CD (88.1% and 70.0%), had injuries due to external causes (84.8% and 68.6%), were involved in fights or assaults (71.2% and 50.0%), attempted suicide (45.8% and 15.8%) and were in controlled environments throughout life (72.9% and 57.1%). Sociodemographic features were similar between patients with or without comorbidities, and also between those with different periods of abstinence. Most patients (59.4%) had negative feelings about their own use of PAS. Conclusion: Two thirds of the patients had a MBD comorbidity diagnosis, which was more frequent among those with shorter periods of abstinence, which shows that sometime of abstinence should be awaited before these diagnoses are given as final. Presence of comorbidities was associated with worse clinical conditions and no differences were found regarding socio-demographic data between the patients with or without comorbidities. Among all, there was a predominance of negative feelings over their own use of PAS.